STUDY OF THE PERFORMANCE OF ROTARY CULTIVATOR ON SOME PHYSICAL PROPERTIES OF SOIL AND FIELD PERFORMANCE CRITERIA - Mothana A. Al-Jarrah (Mesopotamia Journal of Agriculture)
The experiment was carried out at fields of college of agriculture and forestry, university of Mosul to study the effect of two forward speeds (2.22 and 4.95) km/hr and three states of rear shield of rotary cultivator (narrow, medium and wide) on number of soil agregates 5cm/m2, bulk density, porosity, cutting depth, cutting width, practical forward speed, volume of disturbing soil, slippage percentage, coefficient of cutting width and weed control percentage. Results showed that the effect of interaction between forward speeds and rear shield states was significant in all studied characteristics except the bulk density, porosity and slippage percentage. The speed 2.22 km/hr showed higher significance in the number of soil agregates 5cm/m2, cutting depth, cutting width, coefficient of cutting width and weed control percentage. The narrow state of rear shield showed higher significance in the number of soil agregates 5cm/m2. The weed control percentage was increased whereas the distance of rear shield from rotor shaft was increased.